Ergonomics New Insights - Korhan, Orhan (IntechOpen, 2023)
Despite technological advancements, the human operator is still the most important part of any production system. To increase productivity, quality, and effectiveness within production systems, ergonomics, the study of people's efficiency in their working environment, is crucial. Ergonomics involves three pillars: physical, organizational, and cognitive. In today's technologically competitive production environment, physical ergonomics is evolving into the automation of repetitive manual tasks, and manual handling involving logistics and transportation is being improved by new digital technologies. Organizational ergonomics is moving towards studying the requirements of hybrid production systems where humans and machines are becoming more integrated. Virtual models can facilitate timely interactions and enhance perception, cyber-physical systems are developing new ways for people to interact with machines, the use of augmented reality tools will lessen mental stress, and data exchange between departments is expected to enhance cognitive ergonomics. This book discusses recent advances in each of the three pillars of ergonomics.